2023
DOI: 10.1097/scs.0000000000009735
|View full text |Cite
|
Sign up to set email alerts
|

Perfecting the Outcome of Nasal Bone Fracture in the Pediatric Population With a Navigation System

Tae Hwan Park

Abstract: Background: The trend of using navigation systems for treating facial bone fractures is increasing. Nevertheless, any detailed recommendation on using a navigation system to treat nasal bone fracture has never been discussed. Plastic surgeons are prone to do closed reduction of nasal bone fractures with remnant posttraumatic edema in the pediatric population. This study hypothesized that the navigation system benefits this population’s treatment of nasal bone fractures. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Our previous work revealed that the navigation system significantly advances facial bone fracture reconstruction. [2][3][4] This gives more accurate reconstruction and effective surgical time and human resources operation. As of August 18, 2022, the Ministry of Health and Welfare of South Korea officially approved the use and coding navigation in orbital wall fractures as the New Health Technology Assessment System.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous work revealed that the navigation system significantly advances facial bone fracture reconstruction. [2][3][4] This gives more accurate reconstruction and effective surgical time and human resources operation. As of August 18, 2022, the Ministry of Health and Welfare of South Korea officially approved the use and coding navigation in orbital wall fractures as the New Health Technology Assessment System.…”
Section: Discussionmentioning
confidence: 99%
“…With the above theoretical advantages, our current study aims to show the actual process of this procedure in a concise video clip. Our previous work revealed that the navigation system significantly advances facial bone fracture reconstruction 2–4 . This gives more accurate reconstruction and effective surgical time and human resources operation.…”
Section: Discussionmentioning
confidence: 99%